Endostatin attenuates PDGF-BB- or TGF-β1-induced HSCs activation via suppressing RhoA/ROCK1 signal pathways [Erratum] - Ren H; Li Y; Chen Y; Wang L (Dove Medical Press, 2019)
Ren H, Li Y, Chen Y, Wang L. Drug Des Devel Ther. 2019; 13:285–290.On page 289, Figure 4 and Notes should read as follows:Figure 4 Endostatin inhibits the expression of α-SMA, RhoA, and ROCK1 at mRNA level.Notes: Transcript levels of α-SMA, RhoA, and ROCK1 were analyzed by RT-PCR (A–C). Endostatin significantly suppressed the expressions of α-SMA, RhoA, and ROCK1 at mRNA level in HSC-T6 cells. Data are expressed as mean ± SD. *P<0.05, **P<0.01 (n=3 per group).Abbreviations: α-SMA, α-smooth muscle actin; GAPDH, glyceraldehyde 3-phosphate dehydrogenase; HSC, hepatic stellate cell; RhoA, ras homolog gene family, member A; ROCK1, Rho-associated protein kinase 1; RT-PCR, real-time PCR.Read the original article